Intensification of photocatalytic pollutant abatement in microchannel reactor using TiO2 and TiO2-graphene - Natan Padoin (2016)
A microfluidic device was applied to the photocatalytic degradation of methylene blue as a model pollutant. Titaniumdioxide nanoparticles (TiO2-P25) and a synthesized composite TiO2-graphene catalyst were immobilized on the innerwalls of a borosilicate glass microfluidic chip. The deposition evolution of the nanoparticles was evaluated by monitoring the optical profile of the system. It was found that a higher initial reaction rate was obtained in the microreactorcontaining composite catalyst (TiO2-GR) on the inner walls, but both systems (TiO2 and TiO2-GR) achieved similarreaction rates when the steady-state was reached. Decolorization rate of methylene blue in our microfluidic chips wasfound to be approximately one order of magnitude higher than equivalent macroscopic systems reported in the literatureat similar experimental conditions. Additionally, computational simulations were performed to investigate the physicsinvolved in these processes. The model was experimentally validated for further scale-out studies.